1995
DOI: 10.1080/00908319508946074
|View full text |Cite
|
Sign up to set email alerts
|

Physical Structure Changes of Canadian Coals During Combustion

Abstract: Three coals were combusted in the Alberta Research Council laminar flow combustor in order to understand the changes in the physical structure that occur during pulverized coal combustion. A subbituminous (coal A), and both high-volatile (coal B) and low-volatile bituminous (coal C) coals were chosen to examine coals of different rank and reactivity.The subbituminous coal and the high-volatile bituminous coal were very reactive, with burnouts of 95% and 88% achieved under stable operating conditions. The low-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It's been observed that such settings guarantee homogeneity of ignition and prevents decripitation (this effect was not observed for particulates bigger than 385 μm mean size) 41 . Gentziz and Chambers 42 and De Soete 43 observe that coal particulate sizes higher than 100 μm and heating rates below 600 o C/min favor homogeneous ignition. It is known that higher heating rates cause larger temperature gradients throughout the sample, thereby affecting kinetics (see for instance 27,44 ).…”
Section: Methodsmentioning
confidence: 99%
“…It's been observed that such settings guarantee homogeneity of ignition and prevents decripitation (this effect was not observed for particulates bigger than 385 μm mean size) 41 . Gentziz and Chambers 42 and De Soete 43 observe that coal particulate sizes higher than 100 μm and heating rates below 600 o C/min favor homogeneous ignition. It is known that higher heating rates cause larger temperature gradients throughout the sample, thereby affecting kinetics (see for instance 27,44 ).…”
Section: Methodsmentioning
confidence: 99%
“…These temperature rates were chosen because they are low enough to favour homogeneous ignition [20] and minimise mass transfer effects. High heating rates cause large temperature gradients throughout the sample, affecting kinetics [21,22].…”
Section: Tg Analysismentioning
confidence: 99%